The Effect of Genotypes and plant distances on leaf miner infestation in pea plant (Pisum sativum L.) - Bakhan Kh. Mohammed; Nadyah S. Wali; Havall M. Ahmed (Agricultural Science, 2022)
Green pea plants are liable to infestation by vegetable leaf miner Liriomyza spp. (Diptera: Agromyzidae) ,is a polyphagous species spread around the world, becoming vegetable crop pests.  An experiment was carried out in the directory of agricultural research, Iraq, Sulaimanyah in Plant Protection Research Station in Bakrajo region during season 2020 to study the effect of different genotypes and planting spaces on the population density of Leaf miner infesting pea plants. The obtained results revealed that the population density of leaf miner on pea plants not differed significantly according to the planting spaces (5cm, 15cm and 25cm) during the season. Planting of pea seeds in the planting space (5cm) population density of leaf miner decreased by the first planting space (%16.895). The pea plants were sown in the planting space (15cm) infested by the highest level of the insect (leaf miner) (%18.452) followed by pea plants sowing at the planting space (25cm) which infestation level was (%17.967) respectively. for the physical characters of the plant (plant high, total weight and weight of 100 grains) the results shows that the sowing pea in the spacing of (15cm) were significantly difference, followed by (5cm) while planting distance of (25cm) showed lowest levels of result for last three parameters.